Photoreleasable ligands to study intracrine angiotensin II signalling. (7th January 2015) - Tadevosyan, Artavazd; Létourneau, Myriam; Folch, Benjamin; Doucet, Nicolas; Villeneuve, Louis R.; Mamarbachi, Aida M.; Pétrin, Darlaine; Hébert, Terence E.; Fournier, Alain; Chatenet, David; Allen, Bruce G.; Nattel, Stanley
Abstract : Key points: The renin–angiotensin system plays a key role in cardiovascular physiology and its overactivation has been implicated in the pathogenesis of several major cardiovascular diseases. There is growing evidence that angiotensin II (Ang‐II) may function as an intracellular peptide to activate intracellular/nuclear receptors and their downstream signalling effectors independently of cell surface receptors. Current methods used to study intracrine Ang‐II signalling are limited to indirect approaches because of a lack of selective intracellularly‐acting probes. Here, we present novel photoreleasable Ang‐II analogues used to probe intracellular actions with spatial and temporal precision. The photorelease of intracellular Ang‐II causes nuclear and cytosolic calcium mobilization and initiates the de novo synthesis of RNA in cardiac cells, demonstrating the application of the method. Abstract: Several lines of evidence suggest that intracellular angiotensin II (Ang‐II) contributes to the regulation of cardiac contractility, renal salt reabsorption, vascular tone and metabolism; however, work on intracrine Ang‐II signalling has been limited to indirect approaches because of a lack of selective intracellularly‐acting probes. Here, we aimed to synthesize and characterize cell‐permeant Ang‐II analogues that are inactive without uncaging, but release active Ang‐II upon exposure to a flash of UV‐light, and act as novel tools for use in the study of intracrine Ang‐II physiology. We prepared three novel caged Ang‐II analogues, [Tyr(DMNB) 4 ]Ang‐II, Ang‐II‐ODMNB and [Tyr(DMNB) 4 ]Ang‐II‐ODMNB, based upon the incorporation of the photolabile moiety 4, 5‐dimethoxy‐2‐nitrobenzyl (DMNB). Compared to Ang‐II, the caged Ang‐II analogues showed 2–3 orders of magnitude reduced affinity toward both angiotensin type‐1 (AT1R) and type‐2 (AT2R) receptors in competition binding assays, and greatly‐reduced potency in contraction assays of rat thoracic aorta. After receiving UV‐irradiation, all three caged Ang‐II analogues released Ang‐II and potently induced the contraction of rat thoracic aorta. [Tyr(DMNB) 4 ]Ang‐II showed the most rapid photolysis upon UV‐irradiation and was the focus of subsequent characterization. Whereas Ang‐II and photolysed [Tyr(DMNB) 4 ]Ang‐II increased ERK1/2 phosphorylation (via AT1R) and cGMP production (AT2R), caged [Tyr(DMNB) 4 ]Ang‐II did not. Cellular uptake of [Tyr(DMNB) 4 ]Ang‐II was 4‐fold greater than that of Ang‐II and significantly greater than uptake driven by the positive‐control HIV TAT(48–60) peptide. Intracellular photolysis of [Tyr(DMNB) 4 ]Ang‐II induced an increase in nucleoplasmic Ca 2+ ([Ca 2+ ]n ), and initiated 18S rRNA and nuclear factor kappa B mRNA synthesis in adult cardiac cells. We conclude that caged Ang‐II analogues represent powerful new tools for use in the selective study of intracrine signalling via Ang‐II.